Clinical Features of Chronic Nasal Polyposis and Assessment of Conservative Treatment Effectiveness (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the morphological characteristics of angiogenesis in nasal polyps and their correlation with pathological changes. The study aimed to evaluate the extent of new blood vessel formation in polyp tissues, their structural and functional state, as well as to determine the proliferative activity of endothelial cells. Microscopic, histological, and histochemical analyses revealed that the activation of angiogenesis is intricately linked to inflammatory, regenerative, and fibroplastic reactions observed in the tissues.